Horas sin lastre (1941): Una antología poética manuscrita en la Prisión “Fuerte de San Cristóbal” - García Monge, Carlos (Huarte de San Juan. Filología y Didáctica de la Lengua, 2011)
This article presents a hitherto unpublished manuscript that was written by Felipe Monge in the prison “Fuerte de San Cristobal” in Pamplona, during the years that followed our Civil War. The article reveals the unpublished poems included in this manuscript, entitled “Horas sin lastre” and points out some of the poetry readings to which political prisoners had access in “Fuerte de San Cristobal”.